Origin of the Extended Mars Radar Blackout of September 2017. Issue 6 (6th June 2019) - Sánchez–Cano, Beatriz; Blelly, Pierre‐Louis; Lester, Mark; Witasse, Olivier; Cartacci, Marco; Orosei, Roberto; Opgenoorth, Hermann; Lillis, Robert; Leblanc, François; Milan, Stephen E.; Conroy, Philip; Floury, Nicolas; et al.
Abstract: The Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) onboard Mars Express, which operates between 0.1 and 5.5 MHz, suffered from a complete blackout for 10 days in September 2017 when observing on the nightside (a rare occurrence). Moreover, the Shallow Radar (SHARAD) onboard the Mars Reconnaissance Orbiter, which operates at 20 MHz, also suffered a blackout for three days when operating on both dayside and nightside. We propose that these blackouts are caused by solar energetic particles of few tens of keV and above associated with an extreme space weather event between 10 and 22 September 2017, as recorded by the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission. Numerical simulations of energetic electron precipitation predict that a lower O2 + nighttime ionospheric layer of magnitude 10 10 m − 3 peaking at 90‐km altitude is produced. Consequently, such a layer would absorb radar signals at high frequencies and explain the blackouts. The peak absorption level is found to be at 70‐km altitude. Plain Language Summary: Several instrument operations, as well as communication systems with rovers at the surface, depend on radio signals that propagate throughout the atmosphere of Mars. This is the case also for two radars that are currently working in Mars' orbit, sounding the ionosphere, surface, and subsurface of the planet. In mid‐September 2017, a powerful solar storm hit Mars, producing a large amount of energetic particle precipitation over a 10‐day period. We have found that high‐energy electrons ionized the atmosphere of Mars, creating a dense layer of ions and electrons at 90 km on the Martian nightside. This layer attenuated radar signals continuously for 10 days, stopping the radars to receive any signal from the planetary surface. In this work, we assess the properties of this layer in order to understand the implications of this kind of phenomenon for radar performance and communications. Key Points: A large space weather event caused negatively impacted radar performance for 10 days Solar electron precipitation created a low ionospheric layer at 90 km on the nightside The nightside ionization is comparable to dayside values